Composition in portraits: Selfies and wefies reveal similar biases in untrained modern youths and ancient masters*. Issue 3 (4th May 2017) - Bruno, Nicola; Bode, Carole; Bertamini, Marco
ABSTRACT: Previous analyses suggest that artists prefer poses showing the left side of the subject's face when composing a portrait, but showing the right side when composing their own self-portrait. There is also some evidence that artists may prefer compositions with key features on the right of the picture. Do these findings generalize to spontaneous, pseudo-artistic productions by individuals with no formal training in painting and art history? To investigate this issue, we tested a sample of 104 British schoolchildren and teenagers (mean age = 13.8 years; 80 females). We analysed posing biases in individual photographic self-portraits ("selfies") as well as of self-portraits including also the portrait of a friend ("wefies"). Our results document a bias for showing the left cheek in selfies, a bias for placing the selfie-taker on the right in wefies, and a bias for showing two left cheeks over two right cheeks, again in wefies. These biases are reminiscent of what has been reported for selfies in adult non-artists and for portraits and self-portraits by artists in the 16th–18th centuries. Thus, these results provide new evidence in support of a biological basis for side biases in portraits and self-portraits independently of training and expertise.